Kualitas Media Agar Darah Manusia dan Domba pada Pertumbuhan Streptococcus β hemolyticus: Quality of Human and Sheep Blood Agar Media on the Growth of Streptococcus β hemolytic - Mochamad Rizal Maulana; Maseva Wijayanti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Sheep blood agar (ADD) is a growth medium for identifying pathogenic bacteria and is a standard medium for microbiological examination. Some countries experience difficulties multiplying ADD due to several factors, so another alternative is needed: using human blood agar (ADM) as a substitute. This study examines the feasibility of ADM as an alternative medium to replace ADD in growing Streptococcus β hemolyticus. This study used sheep and human blood agar, which were then observed at 24 and 48 hours of incubation to show differences in hemolysis in diameter. At 24 hours, the average hemolytic diameter of ADM did not show hemolysis (0.00mm) and was different from ADD (0.40mm). ,10mm). Based on the above results, in the future, it is necessary to control other variables that might influence, such as Hb and age of erythrocytes, agar thickness, pH used, and planting techniques (strict) to obtain maximum growth results.